2017
DOI: 10.1111/ppe.12380
|View full text |Cite
|
Sign up to set email alerts
|

Association between PM2.5 and PM2.5 Constituents and Preterm Delivery in California, 2000–2006

Abstract: PM constituents ammonium, nitrate and bromine, often linked to traffic and biomass combustion, were most associated with increased risk of preterm delivery in California. Certain demographic subgroups may be particularly impacted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 42 publications
0
22
1
Order By: Relevance
“…Most studies highlighted the importance of particulate air pollution exposure in the late pregnancy period. 33 , 53 55 In this study, we also identified the third trimester to be the sensitive window for particulate air pollution to act on gestation duration compared with the other two trimesters, indicating that PM 2.5 can trigger delivery through uterine infection. Effect estimates were even larger for the exposure window of preceding month before delivery.…”
Section: Discussionmentioning
confidence: 63%
“…Most studies highlighted the importance of particulate air pollution exposure in the late pregnancy period. 33 , 53 55 In this study, we also identified the third trimester to be the sensitive window for particulate air pollution to act on gestation duration compared with the other two trimesters, indicating that PM 2.5 can trigger delivery through uterine infection. Effect estimates were even larger for the exposure window of preceding month before delivery.…”
Section: Discussionmentioning
confidence: 63%
“…The literature review found an association between this toxic agent and fertility among couples, especially in male groups. According to some reports, pregnancies may be affected by some adverse events [16,17,19].…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Basu et al stated that the risk of preterm labor is higher among pregnant women exposed to ammonium nitrate (ammonium 21.2%, nitrate 18.1% [19]. They also reported a greater incidence in Blacks, Asians and older mothers.…”
mentioning
confidence: 99%
“…Peripheral and cord blood samples were also collected to investigate gene-environment interactions [6] 3 24 h household PM 2.5 exposure during pregnancy PM 2.5 PM 2.5 exposure in pregnancy was associated with 4 g decrease in birth weight while 2% increase in its prevalence. [7] 4 Association between prenatal exposure to PM 2.5 and its constituents and preterm delivery PM 2.5 and PM 10 , ammonium, chlorine, sodium, nitrate, vanadium and bromine Increased risk of preterm delivery with full gestational exposure to PM 2.5 and its constituents; preterm delivery were observed for blacks, Asians and older mothers [8] Exposure to all air pollutants was associated with SGA; proximity to highways was related with 26% increase in SGA and 11% increase in LBW. PM 2.5 exposure with preterm births was observed at <37 weeks and for other pollutants at <30 weeks of gestation [9] 6…”
Section: And Air Toxicantsmentioning
confidence: 99%